Eficácia dos parâmetros do tratamento industrial na tratabilidade e durabilidade de madeiras de eucalipto - Lopes, Dercilio Junior Verly (2014)
The objective of this study was to evaluate the effectiveness of industrial preservative treatment with CCA type C in fence posts of Corymbia torelliana and Eucalyptus grandis x Eucalyptus urophylla. The effectiveness of the preservative treatment has been established by the parameters used in the full-cell process, as initial and final vacuum of 550 mmHg for 30 minutes, the autoclave pressure of 11 kgf.cm-2 (1.07 MPa) for one hour, and 2% of active ingredient CCA (oxic base). The pieces of Corymbia torelliana were from a plantation aged 11, propagated by seed and Eucalyptus grandis x Eucalyptus urophylla, a plantation aged 9 years. Both woods were from commercial plantations located in Pinheiros, Espírito Santo, Brazil. We evaluated 108 fence posts, 54 of each species in wet intervals between 15 to 20%; 20 to 30% and above 30% and three diameter classes, 8 to 10 cm, 10 to 12 and 12 cm to 14 cm. These fence posts 54, 36 of each species were separated for the preservative treatment and 18 untreated to compare the durability properties of the wood, and specific gravity. Were analyzed penetration, retention and resistance to fungi Postia placenta, Gloeophyllum trabeum and Trametes versicolor and termite Nasutitermes corniger the forced feeding test and food preference. The results indicated differences between basic and specific gravity,% heartwood and sapwood, heartwood ratio: sapwood. In general the copper penetration proved to be deep and regular, regardless of moisture content and diameter class. The retention of CCA active ingredients classifies the wood to ground contact. The effect of the preservative treatment conferred increased resistance to the fence post against termites Nasutitermes corniger in both tests, especially in the forced feeding test where the weight loss was less. The wear assigned to the specimens registered the best grades in diameter class 8-10 cm in both radial depths. The parameters used in the preservative treatment provided the wood classified as "highly resistant" against the three tested fungi. The untreated wood were classified as "moderately resistant". In general, species were less resistant to white-rot fungus, Trametes versicolor. The apparent density, moisture content by the resistive method and treatable volume showed no correlation with retention of CCA. On the other hand the weight loss caused on the feeding preference test showed significant negative correlation for both species.